1996
DOI: 10.1203/00006450-199607000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Postjatal Intestinal Maturation by Growth Hormone: Studies in Rats with Isolated Growth Hormone Deficiency

Abstract: During the 3rd wk of postnatal life in the rat, dramatic maturational changes occur in the structure and function of the small intestine, enabling the animal to make the transition from milk to solid food. To investigate the role of GH in the regulation of this complex process, we studied postnatal intestinal maturation in the spontaneous dwarf rat, a strain of Sprague-Dawley rats with an autosomal recessive mutation in the GH gene resulting in complete but isolated GH deficiency. GH-deficient and GH-normal li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The mechanism that regulates or influences the maturational changes in mucosal protection is not known [11,[17][18][19]. We hypothesized that the dietary change from maternal milk to rat chow has some role in maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism that regulates or influences the maturational changes in mucosal protection is not known [11,[17][18][19]. We hypothesized that the dietary change from maternal milk to rat chow has some role in maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of mRNA specific for amylase, lipase and trypsin increase 10-, 8 [91]. Growth hormone is not required for normal postnatal maturation of the small intestine, although it acts by promoting homeostasis or steady-state regulation of mucosal epithelial growth [21]. Somatostatin and luteinizing releasing hormone (Lh-RH) inhibit the proliferation of gastric epithelium cells in rats [27].…”
Section: Effect Of Age On Digestive Productions and Enzyme Expressionsmentioning
confidence: 99%
“…This is comparable to the findings of Ronge and Blum [13] who described that in new-born calves GH concentrations tended to decrease during the first five weeks of life. The high concentrations of GH may have a comparable action a) on the increase in the depth of crypts and b) on the rate of proliferation of the villi of the gut [14]. In this study GH concentrations were elevated before symptoms of diarrhea could be observed.…”
Section: Discussionmentioning
confidence: 52%